Review on security issues and solutions in cloud computing. (3rd October 2022) - Ledwani, Devanshi; Saini, Himanshi; Ledwani, Lalita; Bhagirath, Swami Nisha; Bhatnagar, Vaibhav
Abstract: Cloud computing is the on-demand availability of a group of networked elements providing services, especially data storage and computing power, without actual management and addressing by the user. In lieu, the entire suite of hardware and software is managed by a provider and have functions dispersed over various location, each location being a data center. Since cloud computing users rely on sharing resources and may request multiple cloud services concurrently, a dynamic provision must be there so that all the resources are available to the user in a competent manner. However, despite abundantly available benefits, many organizations are still skeptical about using the cloud computing service model because of security concerns associated with the service. The paper also discusses different types of cloud security, controls of cloud security and algorithms used for emanating the privacy of the client's data. In this paper, a CNN and SVM model is also applied for detection Anti-Spoofing images for identification on images on cloud.